HAK ASASI MANUSIA VIS A VIS PEMBANGUNAN: BERTEMUNYA KEPENTINGAN INDIA, CINA DAN MYANMAR - sugiarto . pramono (Universitas Wahid Hasyim Semarang, 2014)
AbstractHuman rights emerged as a global issue at least the post-cold war. Almost all countries in the world recognized human rights principles. Various attempts were made by countries and various International Non-Governmental Organizations who are committed to upholding the values of human rights. Through multilateral negotiations involving the mass media; interestgroups and pressor groups; the academics and civil society to to promote and declare the values of human rights. But, political realism of states in the pursuit of national interests oftenignore the values of human right. The economic growth of India and China are very progressive and make these countries need access to markets, raw materials and energy. those Insistenceencourage the two government closer to the military junta in Myanmar. Though junta in Myanmar to be an actor severe human rights violations. This article came to the conclusion, thegovernment's commitment to the enforcement of human rights shifted when in conflict with economic interests. Two records that appear are: first, the rate of the Indian economy and Chinahas implications for both countries increasingly indifferent to the affairs of human rights in Myanmar; second, there is a symbiotic mutualism relationship between the two countries with Myanmar that could potentially hinder the enforcement of human rights, especially in Myanmar.Keywords: Realism, development, human rights.